2015
DOI: 10.2139/ssrn.2567180
|View full text |Cite
|
Sign up to set email alerts
|

Real Wage Responsiveness to Unemployment in Spain: Asymmetries Along the Business Cycle

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…We find a similar, but less pronounced pattern in Portugal. The policy agenda in these countries should tackle high and volatile job separations rates, likely related to high incidence of temporary contracts and labour market duality, and low wage flexibility, likely related to the collective bargaining system characterised by a high degree of price indexation (Font et al , 2015) and automatic extension of agreements to all firms and workers (Bentolila et al , 2010). The focus in Greece should be on factors determining the (so far high) elasticity of employment with respect to GDP (potentially regulations hindering internal firm flexibility in adjusting hours and content of jobs, Eichhorst et al , 2010), whereas in Italy on factors behind low responsiveness of labour market to output – which cushions the unemployment increase after adverse shocks, but creates a risk of jobless growth.…”
Section: Discussionmentioning
confidence: 99%
“…We find a similar, but less pronounced pattern in Portugal. The policy agenda in these countries should tackle high and volatile job separations rates, likely related to high incidence of temporary contracts and labour market duality, and low wage flexibility, likely related to the collective bargaining system characterised by a high degree of price indexation (Font et al , 2015) and automatic extension of agreements to all firms and workers (Bentolila et al , 2010). The focus in Greece should be on factors determining the (so far high) elasticity of employment with respect to GDP (potentially regulations hindering internal firm flexibility in adjusting hours and content of jobs, Eichhorst et al , 2010), whereas in Italy on factors behind low responsiveness of labour market to output – which cushions the unemployment increase after adverse shocks, but creates a risk of jobless growth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Solon et al (1994) find that women have less procyclical wages than men, in the United States, whereas Hart (2006) finds no such evidence for the United Kingdom. Martins (2007) and Cervini-Plá et al (2015) find that wages are more sensitive to businesscycle fluctuations during recessions in Portugal and the United Kingdom, respectively, whereas the opposite is found by Shin and Shin (2008) for the United States and by Font et al (2015) for Spain.…”
Section: Heterogeneity In the Norwegian Labor Marketmentioning
confidence: 96%
“…Differences across countries and differences across mobility groups are not the only dimensions of heterogeneity that have received attention in the wage cyclicality literature. Analyses have also been performed on whether wage cyclicality varies with demographic groups (e.g., Solon et al, 1994;Hart, 2006;Martins, 2007;De la Roca, 2014) and stages of the business cycle (e.g., Shin and Shin, 2008;Font et al, 2015). The findings in these studies are not unanimous.…”
Section: Heterogeneity In the Norwegian Labor Marketmentioning
confidence: 99%
“…An issue we cannot robustly address here, given the sample period we study includes only one official recession, is whether the wage response to the business cycle is symmetric. Font et al (2015) found some evidence from Spain using a panel of workers that real wages were less responsive in recessions than in expansions, though these asymmetric effects were less pronounced among new hires than among job stayers. In Online Appendix B, we discuss the results of several more robustness checks, which also do not affect our confidence in the main results.…”
Section: Using Other Specifications Of the Regression Modelmentioning
confidence: 99%